1990
DOI: 10.1159/000243187
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Commonly Used Measures of Intrauterine Growth with Estimated Neonatal Body Fat

Abstract: Several morphometric measures have been used to identify infants at greatest risk from aberrant intrauterine growth. 119 near-term infants were studied to answer the more basic question of how well measures, such as birthweight percentile, ponderal index, the body mass index and the weight/length ratio reflect body fat in the neonate. Skinfold thicknesses were measured as an estimate of fat stores. Multiple regression analysis revealed that the weight/length ratio showed the strongest correlation with relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…Skinfold thickness of the triceps, subscapular, abdominal, suprailiac, thigh and medial calf were measured twice with a Lange skinfold calliper (Cambridge Scientific Industries Inc., Cambridge, MD, USA) on the right side, according to standard techniques, and an average of two measurements was determined. Because measurement of skinfold thickness from multiple sites is the simplest method to estimate percentage total body fat (Wolfe et al ., 1990), the sum of skinfold thicknesses from the six sites measured was used to represent adiposity at birth in this study. Body weight was obtained using a standard electrical scale.…”
Section: Anthropometrycontrasting
confidence: 99%
“…Skinfold thickness of the triceps, subscapular, abdominal, suprailiac, thigh and medial calf were measured twice with a Lange skinfold calliper (Cambridge Scientific Industries Inc., Cambridge, MD, USA) on the right side, according to standard techniques, and an average of two measurements was determined. Because measurement of skinfold thickness from multiple sites is the simplest method to estimate percentage total body fat (Wolfe et al ., 1990), the sum of skinfold thicknesses from the six sites measured was used to represent adiposity at birth in this study. Body weight was obtained using a standard electrical scale.…”
Section: Anthropometrycontrasting
confidence: 99%
“…Preadipocytes begin to differentiate into small adipocytes (fewer than 25 microns in diameter) in utero and most adipocytes are of this type at birth (Boulton et al, 1978). Although we did not measure fat cell size, adipose mass or the regional distribution of adipose tissues in our subjects, good correlations have been found between body fat content and these anthropometric parameters, especially the BW/BL ratio in newborns (Wolfe et al, 1990). Although we did not measure fat cell size, adipose mass or the regional distribution of adipose tissues in our subjects, good correlations have been found between body fat content and these anthropometric parameters, especially the BW/BL ratio in newborns (Wolfe et al, 1990).…”
Section: Discussionmentioning
confidence: 89%
“…Roord and Ramaekers (1978) found a correlation between Rohrer's index and the abdominal skinfold thickness. However, Wolfe et al, (1990), in a study of the correlation between Weight/Length, Weight/Length 2 , and Weight/Length 3 indices and the sum of triceps and subscapular skinfolds in 119 neonates, showed that Rohrer's index was least correlated with skinfolds (r ‫ס‬ 0.55). Coefficients for the other indices were very close together with a slight advantage for Weight/Length, respectively, 0.70 and 0.72.…”
mentioning
confidence: 99%